I also think its 4 but im not sure
Answer:
A.
Step-by-step explanation:
Answer:
No Soultion
Step-by-step explanation:
Use the equation
For A. The problem would be set up like so
5 _ -1
--------
4 _ -2
Start by subtracting 5 minus -1 which is 6 because minus a negative becomes a positive then subtract 4 minus -2 which is 6, remember minus a negative becomes a positive, then divide 6/6 to get 1
For B.
-5 _ -0
----------
3 _ -1
Again subtract -5 by -0 which no matter what will be -5. Then make -1 positive because it's a subtracted negative so it becomes 3+1 which gives you 4. Your answer is -5/4
If you need help with the rest message me good luck
Answer:
a = 5
Remainder when p(x) is divided by x+2 = 62
Step-by-step explanation:
Given:
P(x) = x⁴-2x³+3x²-ax+3a-7
When x+1 divides the polynomial p(x) the ramainder is 19.
Applying remainder theorem,
x = -1
p(-1) = 19
Substitute the x = -1 into the polynomial expression
p(-1) = (-1)⁴-2(-1)³+3(-1)²-a(-1)+3a-7 = 19
1+2+3+a+3a-7 = 19
6-7+4a = 19
4a-1 = 19
4a = 19+1
4a = 20
a = 20/4
a = 5.
Hence, a = 5
p(x) = x⁴-2x³+3x²-5x+8
If p(x) is divided by x+2,
Then the remainder is p(-2)
p(-2) = (-2)⁴-2(-2)³+3(-2)²-5(-2)+8
p(-2) = 16+16+12+10+8
p(-2) = 62
Hence the remaider when p(x) is divided by x+2 is 62